CED Standards Meeting Diverse Needs through Collaboration - Christensen, Kathee M. ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
This paper presents the views of a member of the committee of the Council for Exceptional Children/Council on Education of the Deaf on professional standards. It addresses the professional challenges suggested by these new standards, including collaboration among university programs, state agencies, and local districts to establish compatible standards documents and application of these standards documents to the development of comprehensive state-of-the art teaching/learning plans. Other topics discussed include the assessment of student outcomes and qualitative teacher assessments; the collaboration among professionals with diverse viewpoints; the resolution of the controversy between English and American Sign Language instruction by using whichever communication method is most effective with a given student; and the development of the collaborative mission of the Council on Education of the Deaf. Analysis of the standards found that one-third of the 66 knowledge and skills statements made specific reference to teamwork or professional collaboration. Collaboration is seen as the ultimate challenge posed to the profession by the standards. (DB)
ERIC Note: In: Windows - 97 on the New Standards. Monograph of Collected Papers from the Annual Conference of the Association of College Educators - Deaf and Hard of Hearing (23rd, Santa Fe, NM, March 7-10, 1997); see EC 305 461.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agency Cooperation; American Sign Language; Cooperative Programs; Deafness; Educational Cooperation; Elementary Secondary Education; Government School Relationship; Hearing Impairments; Higher Education; Interdisciplinary Approach; Professional Development; School Districts; Standards; State Boards of Education; Teacher Collaboration; Teacher Education; Teacher Qualifications; Theory Practice Relationship; Council on Education of the Deaf; Council for Exceptional Children; Opinion Papers; Speeches/Meeting Papers